Effects of 24-Epibrassinolide on Shoot Tip Cultures Under NaCl Stress in Tomato (Solanum lycopersicum L.) - Betül Bürün; Emel Yılmaz Gökdoğan (Journal of Agricultural Sciences)
The negative effects of salt stress on plants and their environment are increasing dramatically day by day, and it is crucial for plants to develop salt tolerance with various applications and biotechnological approaches. For this purpose, it is possible to improve salt tolerance in plants through different studies using controlled and uniform in vitro cultures, which are an alternative approach to greenhouse and pot experiments that affected by external environmental conditions. In this study, 24-epibrassinolide (24-epiBL) was used for increasing salt tolerance in in vitro shoot tip cultures of tomato M-28 hybrid cultivar. Shoot tips of 10-day sterile seedlings were placed in MS medium supplemented with 2 mg L-1 K + 0.4 mg L-1 NAA in a 12-day culture period, and 12-day plantlets soaked in 24-epiBL solutions (0, 1, 2 μM) were transferred to MS medium containing different concentrations of NaCl (0, 20, 40, 60, 80, 100 mM). After 20 days, the plantlets derived from in vitro cultures were used to assess growth (length, fresh and dry weight of plantlets) and biochemical parameters (pigment, MDA, proline, total soluble protein contents, POX and SOD enzyme activities). All growth and biochemical parameters, including pigment and total soluble protein content, were adversely impacted by salt stress (particularly at 40, 60, 80, and 100 Mm NaCl concentrations). However, MDA, proline content, as well as SOD and POX enzyme activity, increased as a results of oxidative stress at the same NaCl concentrations. As a result, NaCl responses in plant differed between various NaCl and 24-epiBL concentrations, and the different defense strategies combine multiple tolerance mechanisms. Therefore, this study, indicates that pretreatment of 24-epiBL to plantlets derived from shoot tips of the tomato M-28 hybrid cultivar played crucial role in mitigating the effects of salt stress.